Rancang Bangun Aplikasi Sistem Informasi Geografis Objek Wisata Buatan Di Bandar Lampung Berbasis Android - Stevani Natasiyah; Rakhmat Dedi Gunawan; Yuri Rahmanto (Jurnal Media Celebes, 2023)
Artificial tourism objects are one of the categories of tourism objects in Bandar Lampung and are widely spread in various sub-districts. While the available information related to location, direction, road conditions, and also existing facilities are not widely known by foreign and local tourists. Therefore, the researcher proposes to build a geographic information system that will assist tourists in searching and finding information related to artificial tourist objects in Bandar Lampung. The system was built using the Protoype method as a system development method, and UML as a system design modeling method. In creating User Interface and building mobile applications using Flutter framework with Dart programming language, while the text editor and software used are Visual Studio Code and Android Studio. The results of testing conducted using the ISO 25010 method show that the Functional Suitability aspect is 100%, and the Usability aspect is 88.27% which can be concluded that the software is acceptable and has met the quality of software feasibility standards.